Pengelolaan Arsip Inaktif Internal Di Dinas Perpustakaan Dan Kearsipan Daerah Kabupaten Banyuasin - Intan Kesuma Fitri; Rusmiatiningsih Rusmiatiningsih (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2020)
This study discusses the Management of Internal Inactive Records in the Banyuasin District Library and Archives Service. This study aims to determine how the management of internal inactive records in the Banyuasin District Library and Archives Service, as well as any obstacles encountered in managing the internal inactive records and their coping efforts at the Banyuasin District Library and Archives Service. This research uses a qualitative descriptive research type. The data collection methods in this research are in the form of observations, interviews, and documentation. Information in this research is, one Head of Archive Management Division, one Head of Dynamic Records Management Section and one Manager of Household Infrastructure and Services. The results of this study indicate that the process of managing internal inactive records in the Banyuasin District Library and Archives Service has implemented a life cycle or record life cycle manually. In addition, it has also implemented semi-automation, namely by applying the transfer of archive media. The constraints faced in managing the internal inactive records are Human Resources / Archivists who are lacking, have not carried out annihilation, and have not re-used the automation system.